Voluntary disclosure of digitalisation-related information by Malaysian public listed companies / Sharifah Norhafiza Syed Ibrahim ...[et al.] - Syed Ibrahim, Sharifah Norhafiza; Shamsudin, Adriana; Ibrahim, Mohd Tarmizi; Jaaffar, Mohd Yassir; Abdullah, Salina; Bani, Hamidah (Universiti Teknologi MARA, 2022)
As digitalisation is costly and requires continuous planning, updating, and monitoring, voluntary disclosure of digitalisation-related information can enhance a company’s reputation and subsequently reduce the cost of capital. However, such information is not part of mandatory disclosure. This paper intends to assess how and how much Malaysian public listed companies disclose digitalisation-related information in their annual reports. Using a qualitative approach and purposive sampling, this study analysed data from the audited annual reports in 2020. Forty-nine Malaysian listed companies were selected. This study discovered that digitalisationrelated information was included in nine sections: overview, events and highlights, management reports and discussion, our capitals, governance and leadership, sustainability report, external environment, notes to the accounts, and additional information. In addition, those disclosures were related to marketing, the product offered, business operation, governance, risk management, customer relations, organisational structure, and strategic management. The disclosure level for digitalisation-related information was generally basic where companies provided a brief description of their digitalisation initiatives, tools, and technologies. These findings are useful for internal and external stakeholders, including Malaysian agencies that are directly responsible for transformation into digitalisation in Malaysia. Future research may cover other sectors, employ different research approaches and focus only on integrated reports.